Pengaruh Perbandingan Terigu dan Tepung Millet (Panicum miliaceum L.) Termodifikasi Heat Moisture Treatment Terhadap Karakteristik Roti Manis - Weresni, Ni Made; Kartika Pratiwi, I Desak Putu; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPA, 2023)
Sweet bread is a type of flour-processed product that has a sweet taste, soft texture, and a variety of shapes. This study was aimed to determine the effect of ratio of wheat and millet flour modified by heat moisture treatment on characteristic of sweet bread and to find out the right of the ratio to produce sweet bread with the best characteristic. This research used Completely Randomized Design with a treatment of ratio between wheat flour and millet HMT flour that consisted of 6 levels namely 100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%:40%, 50%:50%. The data obtained were analyzed by variance at 95% confidence level, and if the treatment had a significant effect then it was followed by the Duncan's Multiple Range Test (DMRT). The result showed that the ratio between wheat and millet HMT flour had a significant effect on moisture content, protein content, and crude fiber content for the sweet bread, also had significant effect on swelling power, color intensity, scoring test (color and texture), hedonic test (color, texture, taste, and overall acceptance) for the sweet bread. The ratio of 80% wheat and 20% millet HMT flour had the best characteristic of sweet bread with moisture content 23.39%, protein content 9,24%, crude fiber content 4,28%, swelling power 194.59%, color intensity L* 70.63, a* 4.33, b* 25.00, with sensory characteristic of sweet bread browny-yellow color, soft texture, and hedonic for aroma, texture, taste, and overall acceptance is liked. Keywords: Millet HMT flour, wheat, sweet bread